Association of 25(OH)D Serum Level with Degree of WOMAC Index in Elderly Female Patients with Knee Osteoarthritis at KPKM FK UIN Jakarta - Ananda Hadist Wahyudi; Achmad Zaki; M. Djauhari Widjajakusumah; Syarief Hasan Lutfie; Muniroh Muniroh (The Avicenna Medical Journal, 2021)
Background. Osteoarthritis (OA) is a chronic, progressive, degenerative disease which incidence increase with age dan occured majority in female. Pain in OA occurs due to accumulative process of degradation, repairment, and inflammation that causes symptoms of pain accompany with decrease in joint activity and function. These symptoms in elderly people, count about 9,8% of Indonesian population in 2020 which is muslim in majority, often causing complaints of difficulties to perform certain movements in shalat. Vitamin D is a nutritional factor which is known from several research wouldinhibit progressive joint destruction and relief of painful symptoms. And may have an important role to prevent the progressive process of the disease, thus promising to help the elderly to perform the shalat without knee joint problems. Objectives. The research’s objective was to determine the association between 25(OH)D serum level and the degree of WOMAC index of pain, stiffness, and functionality of knee OA in elderly female patients at Public Health Clinics (KPKM) Faculty of Medicine, Syarif Hidayatulloh State Islamic University of Jakarta (FK UIN Jakarta). Methods. The research used analytic Cross-Sectional design, with 106 elderly female as respondents, whose pain degree, stiffness, and functionality were measured using the WOMAC questionnaire of Knee OA and 25(OH)D serum level wasexamine. Results. Chi Square Fisher statistical analysis showed that there is no significant statistical association found (p 0,689) between 25(OH)D serum level and the degree of WOMAC index of knee OA in elderly female patients at KPKM FK UIN Jakarta. Conclusion. There is no significant statistical association found between serum vitamin D level and degree of WOMAC index of knee OA in elderly female patients at KPKM FK UIN Jakarta